Un día de nieve - Keats, Ezra Jack. (New York : Scholastic, 1991)
A young black boy spends an adventurous day in the city when it snows.
Translation of: The snowy day.
Keywords: Snow -- Juvenile fiction; African Americans -- Juvenile fiction; Snow -- Fiction; African Americans -- Fiction; Spanish language materials